The Influence Of Organizational Culture And Organizational Support On Civil Servants' Work Ethic Civilians At The Wajok Hulu Outpatient Health Center In Mempawah Regency - Intan Purnama Sari; Irfan Mahdi (UNIVED Press, 2025)
This study aims to determine whether there is a relationship between Organizational Culture (X1), Organizational Support (X2), and Work Ethic (Y). This study is an associative study. The sampling method using the saturated sampling technique obtained 37 samples Civil Servants of Wajok Hulu Outpatient Health Center. Instrument testing uses validity test, reliability test, classical assumption test (normality and linearity), multiple linear regression analysis, multiple correlation coefficient, simultaneous influence test (F-test), and partial test (t-test). Based on the results of the simultaneous test (F-test), there is a significant simultaneous influence between Organizational Culture (X1) and Organizational Support (X2) on Work Ethic (Y) at the Wajok Hulu Outpatient Health Center. The results of the Partial Test (T-test) Organizational Culture (X1) does not have a significant influence on work ethic, while Organizational Support (X2) partially has a significant influence on the variable of Civil Servant Work Ethic at the Wajok Hulu Outpatient Health Center.